EU:n Venäjän vastaisten kauppapakotteiden vaikutus länsimaiden vientiin; The Impact of EU's Trade Sanctions Against Russia on Western Countries Exports - Birgitta Berg-Andersson (The Research Institute of the Finnish Economy (ETLA), 2019)
– EU's trade sanctions against Russia came into force 1.8.2014. Sanctioned products were exported to Russia at a value of 22 billion euros during the time period 2001-2017. The most important exporting countries were Ukraine, China, South Korea, Germany and the United States. Exports of banned products from a country to Russia may be very high in some years and very small in other years. Some products have been exported even during the years 2015-2017 at a value of 2,2 billion euros because export contracts which were made before 1.8.2014 are still in force and the ban on exports of sensitive technology concerns only products, the destination of which is forbidden projects in the oil sector. The exports of the sanctioned products from the whole world to Russia fell substantially in the year 2015 from 1,6 billion euros in the previous year to 0,7 billion euros, which corresponded to the level in 2005. Finland exported banned products to Russia during the years 2001-2017 at a value of 0,57 billion euros. In the years 2010-2011, there were exceptionally big deliveries at a value of 0,2 billion euros. In relation to our total export of goods to Russia, this accounted for a share of 6,6 percent in the year 2010, the corresponding share for the whole world was one percent. In the other years before the sanctions, Finland's percentage share has been substantially smaller than the average share of the whole world and after they have been imposed Finland's share has fallen less than in other countries. We draw the conclusion that Finland has suffered less from the trade sanctions than the rest of the world on average.
Keywords: F13; F14; 330; Trade sanctions; EU; Russia; Exports; Arms